A rat model of valproate teratogenicity from chronic oral treatment during pregnancy. (16th May 2020) - Jazayeri, Dana; Braine, Emma; McDonald, Stuart; Dworkin, Sebastian; Powell, Kim L.; Griggs, Karen; Vajda, Frank J. E.; O'Brien, Terence J.; Jones, Nigel C.
Abstract: Objective: Sodium valproate (VPA), the most effective antiepileptic drug for patients with genetic generalized epilepsy (GGE), is a potent human teratogen that increases the risk of a range of congenital malformations, including spina bifida. The mechanisms underlying this teratogenicity are not known, but may involve genetic risk factors. This study aimed to develop an animal model of VPA‐induced birth defects. Methods: We used three different rat strains: inbred Genetic Absence Epilepsy Rats From Strasbourg (GAERS), a model of GGE with absence seizures; inbred Non‐Epileptic Controls (NEC); and outbred nonepileptic Wistars. Female rats were fed standard chow or VPA (20 g/kg food) mixed in standard chow for 2 weeks prior to conception, and then mated with same‐strain males. Treatment continued throughout pregnancy. Fetuses were extracted via C‐section on gestational day 21 and examined for birth defects, including external assessment and spinal measurements. Results: VPA‐exposed pups showed significant reductions in weight, length, and whole‐body development compared with controls of all three strains ( P  < .0001). Gestational VPA treatment altered intravertebral distances, and resulted in underdeveloped vertebral arches between thoracic region T11 and caudal region C2 in most pups (GAERS, 100%; NEC, 95%; Wistar, 80%), more frequently than in controls (9%, 13%, 19%). Significance: Gestational VPA treatment results in similar developmental and morphological abnormalities in three rat strains, including one with GGE, indicating that the genetic underpinnings of epilepsy do not contribute markedly to VPA‐induced birth defects. This model may be used in future studies to investigate mechanisms involved in the pathogenesis of antiepileptic drug–induced birth defects.